Brain and Spinal Tumors Primary and Secondary - Roy Morgan, Lee; Birol Sarica, Feyzi (IntechOpen, 2020)
Numerous new concepts and procedures are reviewed and discussed in this book and allude to the transport of drugs to the brain. New radiation concepts are also presented, plus management of toxicities associated with both treatment modalities. It is the goal of this book to provide information and data that will be useful for both researchers and practitioners to develop new approaches for the management of CNS malignancies.